2017
DOI: 10.7547/16-157
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Year Review of Clinical Outcome Measures Published in the Journal of the American Podiatric Medical Association and the Journal of Foot and Ankle Surgery

Abstract: This investigation presents a review of all of the clinical outcome measures used by authors and published in the Journal of the American Podiatric Medical Association and the Journal of Foot and Ankle Surgery from January 1, 2011, to December 31, 2015. Of 1,336 articles published during this time frame, 655 (49.0%) were classified as original research and included in this analysis. Of these 655 articles, 151 (23.1%) included at least one clinical outcome measure. Thirty-seven unique clinical outcome scales we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The PROMs reported to be used most often were the AOFAS Ankle-Hindfoot Scale, MFS, AOFAS Midfoot Scale, and FFI, respectively. This research supports previous study outcomes stating that the AOFAS Ankle-Hindfoot Scale is the most popular PROM used in all foot and ankle literature to date [7][8][9][10] . Additionally, it confirms the same is true for literature on foot fractures Furthermore, the calcaneus, talus, Lisfranc joint, and the ossa metatarsalia were analyzed most often.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The PROMs reported to be used most often were the AOFAS Ankle-Hindfoot Scale, MFS, AOFAS Midfoot Scale, and FFI, respectively. This research supports previous study outcomes stating that the AOFAS Ankle-Hindfoot Scale is the most popular PROM used in all foot and ankle literature to date [7][8][9][10] . Additionally, it confirms the same is true for literature on foot fractures Furthermore, the calcaneus, talus, Lisfranc joint, and the ossa metatarsalia were analyzed most often.…”
Section: Discussionsupporting
confidence: 88%
“…Instead, they concluded that for none of the examined instruments this was the case and emphasized the need for a satisfactory one. Four similar studies concluded that a considerable variety of instruments is used in the foot and ankle literature [8][9][10][11] . This is undesirable, especially when the use of different instruments restricts adequate comparison of studies in reviews or meta-analyses [ 9 , 10 ].…”
Section: Responsivenessmentioning
confidence: 99%
“…In 2011, AOFAS published a position statement indicating that their clinical rating system was not considered valid or reliable, advising against its continued use. 19 However, a study conducted in 2017 by Hasenstein et al 20 found AOFAS to be the clinical outcome assessment tool most used by authors and published in medical journals. The Foot and Ankle Outcome Score (FAOS) is a 42-item questionnaire divided into five categories: pain, other symptoms, function in daily life, sports and recreation, and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…During the follow-up period, anterioposterior and lateral X-rays were taken to observe the status of the fracture healing. During the final follow up, functional outcomes were assessed with the American Orthopaedic Foot and Ankle Society (AOFAS) score [ 17 ].…”
Section: Methodsmentioning
confidence: 99%